1982
DOI: 10.1159/000225656
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Related to Ascitic Fluid in Patients with Ovarian Carcinoma

Abstract: The immune response to SRBC (PFC assay) was suppressed in mice injected with cell-free ascitic fluid from patients with ovarian carcinoma. The immunosuppressive effect of ascitic fluid obtained from stage IV patients was stronger than that of stage III patients. These data were correlated with the patient’s immune status (number of E and EAC rosettes, PHA reactivity of lymphocytes, skin reactivity to recall antigens) and with changes in protein fractions in the serum and ascitic fluid. A good correlation was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The degree of suppression of anti-tumor immune activity plays an important role in this context. This study on malignant ascites from OC patients confirms and extends on earlier observations regarding its immunosuppressive properties [16,19]. Inhibitory activity in cell-free ascites was observed against both autologous and allogeneic T cells in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The degree of suppression of anti-tumor immune activity plays an important role in this context. This study on malignant ascites from OC patients confirms and extends on earlier observations regarding its immunosuppressive properties [16,19]. Inhibitory activity in cell-free ascites was observed against both autologous and allogeneic T cells in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that ascites in OC patients is immunosuppressive [13], although the exact mechanism has remained elusive. During the 1980's, experiments showed that malignant ascites was inhibitory in both murine and human models, and many attempts were made to identify and isolate the suppressive factor(s) [13][14][15][16][17][18][19][20]. Earlier independent assessments have recognized the suppressive substance(s) as haptoglobin, carcinoembryonic antigen (CEA) and αglobulin [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported previously that the immunosuppressive activity in human and mouse ascites [19,18] is associated with the alpha and/or beta protein fraction since it has been precipitated at 50% amonium sulfate saturation. In this investigation we have demonstrated the elevation of VLDL which migrates with the pre-beta fraction.…”
Section: Discussionmentioning
confidence: 99%